Forty-two years of scientific research on eight legs-celebrating the 60th birthday of Dr Yuri M. Marusik - Zhang Jianshuang; Mikhailov Kirill G; Koponen Seppo; Long Feiyang; Yu Hao; Li Shuqiang (PENSOFT PUBLISHERS, 2022)
The biography of Dr Yuri Mikhailovich Marusik is presented, and his scientific life illuminated on the occasion of his 60th birthday. Yuri is a renowned specialist of spiders. He has described 718 new species, 57 new genera, and two new subfamilies of order Araneae. Twenty-five species and one genus have been dedicated to him. Facts and impressions are given as well as a bibliography of his 545 publications.